2003
DOI: 10.13057/biofar/f010203
|View full text |Cite
|
Sign up to set email alerts
|

An analgetic activity of sedges (Cyperus rotundus L.) extract on white male mice (Mus musculus L.)

Abstract: The objectives of the research were to find out the effect of giving sedges root extract orally on the number of writhing after chemical pain induction and time reaction after thermal pain induction of mice and also to find out the extract dosage which had an influence on decreasing number of writhing after chemical pain induction and length of reaction time after thermal pain induction of mice. The Complete Random Design (CRD) with 6 treatment groups and each treatment used 5 repetitions were used in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…From the data in the Table 1, it can be seen that the three doses of Sungkai leaf ethanol extract and the positive control (paracetamol) showed that there was a difference in the mean total stretchiness compared to the positive control of 11; 13.8; 12.2; and 8.4 while with a negative control of 27.6. The less the average number of stretches obtained, the better the analgesic effect (Puspitasari et al, 2023;Arifin et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the data in the Table 1, it can be seen that the three doses of Sungkai leaf ethanol extract and the positive control (paracetamol) showed that there was a difference in the mean total stretchiness compared to the positive control of 11; 13.8; 12.2; and 8.4 while with a negative control of 27.6. The less the average number of stretches obtained, the better the analgesic effect (Puspitasari et al, 2023;Arifin et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…An inverse comparison between the mean number of stretches and the percentage of analgetic protection in the test section against the negative control means that the more total stretches the mean, the smaller the percentage of analgetic protection obtained and vice versa (Puspitasari et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…F2 and F3 microcapsules are more than 50%. according to Puspitasari et al (2003). it was stated that they had analgesic activity.…”
Section: Analgesic Activity Testmentioning
confidence: 99%
“…Several species in this family are used in folk medicine (Hibi et al 2019). The studies stated that the extract of the Cyperus rotundus root had an analgesic effect on mice, and its rhizosphere contains bacteria with antimicrobial abilities (Ambarwati et al 2019;Puspitasari et al 2003). Cyperus malaccensis, which has become a vital fiber crop and grown in Japan and China, is the raw material for making mats (Shioya et al 2019).…”
Section: Introductionmentioning
confidence: 99%